2018
DOI: 10.1111/omi.12207
|View full text |Cite
|
Sign up to set email alerts
|

ArcR modulates biofilm formation in the dental plaque colonizer Streptococcus gordonii

Abstract: Biofilm formation and cell-cell sensing by the pioneer dental plaque colonizer Streptococcus gordonii are dependent upon arginine. This study aimed to identify genetic factors linking arginine-dependent responses and biofilm formation in S. gordonii. Isogenic mutants disrupted in genes required for the biosynthesis or catabolism of arginine, or for arginine-dependent gene regulation, were screened for their ability to form biofilms in a static culture model. Biofilm formation by a knockout mutant of arcR, enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…When analyzed the down regulated DEGs, we found a subset of genes, argB, argC, argG, argH, and argJ, all of these arg genes were associated with arginine biosynthesis. Many studies have reported the association between the arginine metabolism and biofilm development in S. sanguinis (Zhu et al, 2017; Nascimento et al, 2019), Streptococcus gordonii (Robinson et al, 2018) , S. aureus and S. mutans (Zhu et al, 2007; Sharma et al, 2014; Huang et al, 2017). Furthermore, another subset of regulated DEGs, comD, comEC, and comX related to the genetic competence system, can also influence biofilm formation which have been reported in S. mutans (Li et al, 2001; Aspiras et al, 2004; Perry et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When analyzed the down regulated DEGs, we found a subset of genes, argB, argC, argG, argH, and argJ, all of these arg genes were associated with arginine biosynthesis. Many studies have reported the association between the arginine metabolism and biofilm development in S. sanguinis (Zhu et al, 2017; Nascimento et al, 2019), Streptococcus gordonii (Robinson et al, 2018) , S. aureus and S. mutans (Zhu et al, 2007; Sharma et al, 2014; Huang et al, 2017). Furthermore, another subset of regulated DEGs, comD, comEC, and comX related to the genetic competence system, can also influence biofilm formation which have been reported in S. mutans (Li et al, 2001; Aspiras et al, 2004; Perry et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Components of a PTS for mannose, sorbose or fructose (SGO_0044–0046) were down-regulated in response to coaggregation. This system has previously been shown to be under the control of the arginine-sensing regulators ArgR and AhrC 44 . However, there was no evidence for a global arginine-sensing response in S. gordonii and arginine biosynthesis genes were not regulated in response to coaggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The arginine repressor is responsible for suppressing arginine deiminase pathways in S. gordonii, and the gene that encodes arginine repressor (SGO_RS03435) was up-regulated (1.58-fold change) (Jakubovics et al, 2015;Robinson et al, 2018). arcA (SGO_RS07805), encoding arginine deiminase, was downregulated (-2.60-fold change).…”
Section: Dual-species Coaggregation Induced Changes In Sources Of Energy Of S Gordoniimentioning
confidence: 99%